RISK MANAGEMENT AND PERFORMANCE OF THE NIGERIAN BANKING INDUSTRY - Joel Obayagbona; Manson Osagiende (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
The study examines the relationship between risk management and the performance of the Nigerian banking industry. The panel data analysis technique based on the fixed effects estimation was employed to analyze the Nigerian banking industry performance. Risk management related factors such as credit risk, liquidity risk, market risk, interest rate risk and operational risk. A total of 18 most active deposit money banks listed on the Nigerian Stock Market for a period of 22 years (2000 to 2021) were used in the analysis. The empirical findings revealed that credit risk and operational risk variables were negative and do not have any significant relationship with the performance of the Nigerian banking industry while liquidity risk and market risk have significant positive effect on bank performance, interest rate risk has significant negative relationship with banks performance in Nigeria within the period of study. The study recommends among others that, banks’ management should have proper understanding of how credit policy affects the operations of their banks to ensure judicious utilization of deposits and maximize profit. Improper credit risk management reduces bank profitability, affects the quality of its assets and increases loan losses and non-performing loan which may eventually lead to financial distress.